MENGGALI SIKAP KEPEMIMPINAN PRIBADI SEBAGAI KECAKAPAN HIDUP BAGI PENGUNGSI - Wijayanti, Sri Hapsari`; Detra, Andreas Elang (Jurnal Bakti Masyarakat Indonesia, 2022)
Personal leadership is a talent that can be learned at any age. At a young age, personal leadership is developed in formal or informal education. In adulthood, leadership can be honed in a work environment or organization. In collaboration with UNHCR in empowering refugees, this community service activity involves refugees living in Jakarta and surrounding areas. Refugees are adults who do not escape to hone their leadership spirit to become strong and independent individuals. They often feel unable to adapt, not knowing what to do best for themselves or others. The purpose of this community service activity is to hone personal leadership attitudes for refugees in fighting for life based on their potential. There are 26 refugees from various countries who attended this activity. Stages of activities include preparation, implementation, and evaluation. In the preparation stage, participants filled out a questionnaire regarding the theory of leadership concepts. In the implementation stage, these activities are held using training methods and lecture techniques, tests, sharing experiences, and interactive discussions. The evaluation phase includes observation and evaluation of test results. Participants classified as adults prefer to discuss their lives related to personal leadership rather than mastering leadership theory as given in the test. The test result shows that the comprehension of leadership increased only 6%. However, this activity received a positive response from the participants. They are motivated to improve themselves and to become their leaders. ABSTRAK: Kepemimpinan pribadi merupakan bakat yang dapat dipelajari di segala usia. Di usia muda, kepemimpinan pribadi dikembangkan di tingkat pendidikan formal atau informal. Di usia dewasa, kepempimpinan dapat diasah di lingkungan kerja atau organisasi. Bekerja sama dengan UNHCR dalam pemberdayaan pengungsi, kegiatan pengabdian kepada masyarakat ini melibatkan para pengungsi yang tinggal di wilayah Jakarta dan sekitarnya. Pengungsi adalah insan dewasa yang tidak luput untuk mengasah jiwa kepemimpinan personal sehingga mampu menjadi pribadi yang kuat dan mandiri. Mereka tidak jarang merasakan ketidakmampuan dalam beradaptasi, tidak mengetahui harus berbuat apa yang terbaik bagi diri sendiri atau orang lain. Tujuan kegiatan pengabdian kepada masyarakat ini adalah mengasah sikap kepemimpinan pribadi bagi para pengungsi dalam memperjuangkan kehidupan berdasarkan potensi diri mereka. Kegiatan ini dihadiri oleh 26 pengungsi dari berbagai negara. Tahapan kegiatan meliputi persiapan, pelaksanaan, dan evaluasi. Dalam tahap persiapan, peserta mengisi kuesioner mengenai teori konsep kepemimpinan. Dalam tahap pelaksanaan, kegiatan dilakukan dengan metode pelatihan dan teknik ceramah, tes, berbagi pengalaman, dan diskusi interaktif. Tahap evaluasi meliputi pengamatan dan evaluasi hasil tes. Peserta yang tergolong dewasa ini lebih suka berdiskusi tentang kehidupan mereka terkait dengan kepemimpinan pribadi dibandingkan dengan menguasai teori kepemimpinan seperti yang diberikan dalam tes. Hal ini diketahui dari hasil tes yang hanya meningkat 6% dari sebelum diberikan materi tentang kepemimpinan. Meskipun demikian, kegiatan ini mendapat respon positif dari peserta. Mereka termotivasi untuk memperbaiki diri dan menjadi pemimpin bagi diri sendiri.